Simulation of photoconductive antennas for terahertz radiation (2015)
Simulation of terahertz (THz) emission based on PC antennas imposes a challenge to couple the semiconductor carrier phenomena, optical transport and the THz energy transport. In this paper a Multi-physics simulation for coupling these phenomena using COMSOL Multi-physics 4.3b is introduced. The main parameters of THz photoconductive (PC) antenna as THz emitter have been reviewed and discussed. The results indicate the role of each parameter in the resulting photocurrent waveform and THz frequency: The radiated THz photocurrent waveform is determined by the photoconductive gap (the separation between the metallic electrodes), the incident laser illumination and the DC excitation voltage; while the THz frequency depends on the dipole length. The optimization of these parameters could enhance the emission. The simulations extend the advance of compact and cost-effective THz emitters.